COORDINATION OF RECLOSERS AND FUSE CUT-OUTS ON 20 kV MEDIUM VOLTAGE OVERHEAD LINES (SUTM) AT THE EBAN FEEDER OF PT.PLN (PERSERO) ULP KEFAMENANU - Rambu, Shindi Anjeline; Likadja, Frans J; Ginting, Almido (Teknik Elektro Universitas Siliwangi, 2025)
The Eban feeder is the longest feeders at PT. PLN (PERSERO) ULP Kefamenanu, with a medium- voltage overhead line length of 60.62 kms. In the distribution system, the Eban feeder is equipped with one Joongwon recloser on the medium-voltage network and 16 Fuse Cut Outs (branch points). This study aims to determine the coordination between the recloser and the Fuse Cut Outs (FCO) on the Eban feeder. The research method used is quantitative descriptive to identify the coordination settings of the recloser and FCO. The test data in this study include recloser settings, FCO ratings, transformer data, load data, CT data, and simulation using Etap 19.0.1. In the event of a short-circuit fault, the Nian recloser will operate first, with a breaking time of 0.521s.